Assessment of the Quality of Life in Patients with Migraine - Pociūtė, S.; Jakavonytė-Akstinienė, A. (Neurologijos seminarai, 2023)
Introduction. Migraine is one of the most common neurological disorders in the world, affecting around 1.1 billion people worldwide. The disease impacts on both physical and mental health, while also reducing the quality of life. The aim of this study was to evaluate the quality of life of patients with migraine and its association with socio-demographic characteristics.Materials and Methods. The study was conducted between November 2023 and January 2024. A total of 370 patients with migraine took part in this study. Patients participated in an anonymous online questionnaire survey. The survey consisted of a two-part questionnaire: 1) demographic data; 2) Short Form 36 Medical Outcomes Study questionnaire (SF-36 questionnaire). Statistical analysis of the data was performed by using Microsoft Office Excel 2010 and SPSS (Statistical Package for Social Science) 24.0 software packages. The results were considered as statistically significant at p<0.05.Results. The majority (95.4%) of the participants were women. The highest scores in the physical health category were physical functioning (77.64±18.95), whereas the lowest scores were given to role limitations due to physical health (38.38±37.99). The highest scoring subscale of mental health was emotional well-being (49.31±18.11), while the lowest scoring subscale was energy/fatigue (43.47±18.20). The quality of life of migraine sufferers is low (48.08±17.85). An older age of migraineurs is correlated with better scores in energy/fatigue (p=0.022) and emotional well-being (p<0.001).Conclusions. Migraine is most prevalent among women. The older a person is, the more positive they are about their energy levels and emotional well-being. The respondents were optimistic about their physical and mental state. The most negative effects of the disease are the lack of energy and vitality along with limitations in activities due to physical health problems. The overall quality of life of the patients is low.